Occupational stress and marital contentment in the COVID-19 era among married tutors of colleges of education - Priscilla Commey-Mintah; Emmanuel Adjei-Boateng; Fred Kofi Boateng; Florence Christianah Awoniyi; Kwaku Darko Amponsah (Intelektual Pustaka Media Utama, 2023)
Occupational stress has been the subject of numerous research studies conducted across the globe due to its impact on our daily life. For instance, it can have a negative impact on teachers’ psychological and normal functioning of the body at all levels as well as their performance. It can even impact adversely on their marriage and social lives as well. This study explored the relationships between occupational stress and marital contentment in the COVID-19 era. The current COVID-19 pandemic, which shook the foundations of labour, industries, and economies worldwide, has exacerbated the crisis of occupational stress among many people, including teachers. The demises, national lockdowns, and general unpredictability caused by the virus have disrupted workflow and made marriages more stressful. As a consequence, this study was based on the numerous sources of occupational stress and the association between occupational stress and marital contentment. With a sample size of 100 out of 132 married tutors from selected Ghanaian colleges of education, the research used a correlational descriptive research approach. The findings revealed that during COVID-19 married tutors faced stressful situations as a result of their expertise and talents not being fully exploited at work. Occupational stress and marital contentment were also found to be somewhat positively related (r=.28). The study also found that there were no gender variations in occupational stress (P=.156) and marital contentment (P=.108) among married tutors.